Epidemiology of Betacoronavirus erinacei infecting European hedgehog (Erinaceus europaeus) in Apulia, Southern Italy: The potential role of mother-offspring groups in viral circulation - Valentina Giordano; Nicola Pugliese; Dario Sciancalepore; Roberto Lombardi; Dalila Salierno; Michela Prioletti; Gaia Casalino; Elena Circella; Antonio Camarda (European Journal of Wildlife Research, 2026)
European hedgehogs ( Erinaceus europaeus ) are recognized reservoirs of Betacoronavirus erinacei , but the mechanisms sustaining viral circulation in largely solitary hosts remain unclear. Therefore, this study aimed to investigate the presence, transmission clues, and phylogenetic relationships of B. erinacei in hedgehogs admitted to a regional wildlife recovery center in Apulia. From May to September 2025, oropharyngeal and rectal swabs were collected from 111 individuals and screened by RT-PCR. The nucleotide sequences of the obtained amplicons were determined, and phylogenetic analysis was performed by the maximum-likelihood method. Overall, 29 out of the 111 animals (26.1%) tested positive. Virus was detected from the rectal swab of all the positive animals, while nine of them were also positive to oropharyngeal swabs. The latter came from juvenile subjects occurring only within mother-offspring groups (MOGs). In positive MOGs, the adult rectal swab was consistently positive, while offspring showed scattered rectal and occasional oropharyngeal positivity, suggesting early oro-fecal exposure within the nest. Phylogenetic analysis revealed that Apulian sequences formed a distinct, well-supported cluster, separate from other Italian and European ones, indicating local circulation of closely related strains. Taken together, these findings suggest that B. erinacei may persist in the study area through transmission within family groups, likely via oro-fecal routes, with juveniles contributing to the viral dissemination. Since infection does not appear to cause evident clinical disease, local maintenance and clonal phylotype distribution can be sustained.